Cultural Industries In The Development Policies Of Cities And Regions: A New Area Of Educationin Spatial Management - Churski, Paweł; Motek, Paweł; Stryjakiewicz, Tadeusz (Quaestiones Geographicae, 2015)
This paper seeks to present organisational and programme assumptions of a new field of postgraduate studies called Cultural industries in the development policies of cities and regions, prepared by a team of workers of the Institute of Socio-Economic Geography and Spatial Management of Adam Mickiewicz University in Poznań as a didactic innovation based on a modular system of education that meets contemporary changes in the labour market. The analysis will also embrace experiences following from the educational process implemented under the Human Capital Operational Programme in the years 2013–2015 (Priority IV: Tertiary Education and Science, Measure 4.3: Enhancing the didactic potential of universities in areas of key importance for the Europe 2020 Strategy). They provide a basis for conclusions and recommendations for higher schools interested in the development of this area of education.